Strategic management and entrepreneurship: Friends or foes? - Sascha Kraus; Ilkka Kauranen (International Journal of Business Science & Applied Management (IJBSAM), 2009)
The objective of this article is to create a better understanding of the intersection of the academic fields of entrepreneurship and strategic management, based on an aggregation of the extant literature in these two fields. The article structures and synthesizes the existing scholarly works in the two fields, thereby generating new knowledge. The results can be used to further enhance fruitful integration of these two overlapping but separate academic fields. The article attempts to integrate the two fields by first identifying apparent interrelations, and then by concentrating in more detail on some important intersections, including strategic management in small and medium-sized enterprises and start-ups, acknowledging the central role of the entrepreneur. The content and process sides of strategic management are discussed as well as their important connecting link, the business plan. To conclude, implications and future research directions for the two fields are proposed.
Keywords: 650; strategy; strategic management; entrepreneurship; small and medium-sized enterprises; SMEs; intersection